The preparation and performance research and application of high performance steel fiber reinforced concrete in deep and large freezing shaft - Jiabao Hu; Zhishu Yao; Yongjie Xu; Rui Wang; Kun Hu (Materials Research Express)
To address the issues of temperature cracks and water leakage in the support structure of deep and large freezing shafts in western China, high-performance concrete incorporating steel fibers and fly ash was proposed as a wall construction material. First, an orthogonal experimental design was conducted by considering three factors: concrete strength grade, steel fiber content, and fly ash content. Based on mechanical performance analysis and range analysis, the optimal mix ratio for deep and large freezing shafts was determined as cement: fly ash: admixture: stone: sand: water: steel fiber = 1:0.15:0.333:2.645:1.488:0.367:0.012. Subsequently, the early crack resistance of both the benchmark concrete and the optimal mix ratio of high-performance steel fiber-reinforced concrete was evaluated using the plate crack resistance method. The optimized mix showed a 910.1% reduction in the total cracking area compared with the benchmark group. Based on the stress environment of the deep frozen shaft wall at the Taohutu Coal Mine, an impermeability test was performed on high-performance concrete after exposure to salt intrusion and freeze–thaw cycles under constant water pressure and varying confining pressure, clarify the impermeability of the optimal concrete mix. The results indicated that the impermeability of the optimal concrete mix under various confining pressures was 39.0%–48.0% lower than that of the benchmark group. The pore structure of the concrete was analyzed using Scanning Electron Microscopy (SEM) and Nuclear Magnetic Resonance (NMR) revealed that the main pore signal amplitude of the optimal mix ratio concrete was 35.9% lower. Finally, field observations confirmed that a cast-in-place shaft wall constructed with optimized CF70 high-performance steel fiber-reinforced concrete exhibited a smooth surface with minimal temperature cracks. These findings validated that optimized CF70 high-performance steel fiber-reinforced concrete was successfully implemented in engineering applications, demonstrating its practical feasibility.